Overexpression of PROM1 (CD133) confers poor prognosis in non-small cell lung cancer - Qiu, Zhi-Xin (Int J Clin Exp Pathol, 2015)
The surface marker PROM1 is considered one of the most important marker of tumor-initiating cells, and its high expression is believed to be an adverse prognostic factor in gliomas, medulloblastoma and in other malignancies. The aims of our research were to explore the expression profile of the PROM1 in non-small cell lung cancer (NSCLC) and to assess its possible role as a prognostic factor. The protein expression profiles were determined via immunohistochemical staining assay. The clinical prognostic values of protein expression were investigated with univariate and multivariate survival analysis. The quantitative variable PROM1 expression was dichotomized according to the best cutoff value obtained by the receiver operating characteristics (ROC) analysis. The protein level of PROM1 of NSCLC was higher compared with normal tissues, and the survival analysis demonstrated the positive membrane expression and combination of membrane/cytoplasm groups of PROM1 had worse prognosis than those negative expression groups. Also, multivariate Cox regression analysis showed membrane expression of PROM1 and lymph node invasion were the independent prognostic factors. The expression of PROM1 was significantly higher than normal tissue, and high levels of PROM1 membrane expression and combination of membrane/cytoplasm expression were associated with adverse prognosis.